Direct benefits of Covid-19 Vaccination at Juata Primary Health Center, North Tarakan District - Harlianti, Mariska Sri; Fortuna, Tista Ayu; Ramadhini, Affida; Aisya, Fitria Shofwa (Universitas Muhammadiyah Surakarta, 2023)
North Kalimantan Province is the only province with a pandemic situation level in the medium level community transmission (CT2) category with an accumulated incidence of 24.1 per 100,000 population in 2021. The increasing incidence is accompanied by opinions of rejection in the community regarding confusion over Covid-19 vaccination at the start of the incident. , underlying the increasing morbidity and mortality rates as well as the decline in the country's social and economic activities. The Covid-19 vaccination program is an effort to reduce morbidity and mortality rates as well as restore social and economic conditions due to the pandemic. The aim of this research is to calculate the direct economic value of the Covid-19 vaccination program. Observational research with descriptive quantitative data analysis was carried out to illustrate this aim. Data collection was carried out retrospectively based on monthly reports from the Juata Community Health Center specifically for Covid-19. The sample inclusion criteria in this study were data on patients who were confirmed positive for Covid-19 in the North Tarakan District area in 2020 – 2022 and received therapy based on the guidelines or Guidelines for the management of Covid-19, 4th edition of 2022. The sample was divided into 3 vaccination periods with the number of samples for each were 77, 92, and 89 patients respectively. The direct benefit of the Covid-19 vaccination program is the difference in total costs between periods. The research results show that the difference in costs for periods I and II and II and III is negative, namely (-) IDR 12,697,280 and (-) IDR 494,660, respectively. Thus, from an economic aspect it does not yet illustrate the direct benefits of the 1 – 3 dose vaccination program. One of the reasons may be the inappropriate use of Covid-19 treatment drugs, namely oseltamivir. However, the incidence of Covid-19 decreased by 34.8% in period III (vaccination doses 2 to 3), namely 417. This shows that from a clinical aspect, the Covid-19 vaccination program is able to increase immunity.